Groundwater sources classification in Costa Rica - Orozco-Gutiérrez, Jimena (2019)
Groundwater sources require previous treatment. Complexity of water purification depends on microbiological and physical-chemical properties of water. The current groundwater classification guidelines are out-of-date, and they do not respond to the aqueduct operators’ needs to determine whether using new groundwater sources is feasible. This document aims to develop a method for classifying potential groundwater sources in Costa Rica according to their complexity for treating and purifying drinking water. This work stablished four categories (A, B, C and D) for classifying potential groundwater sources, along with the maximum limits allowed for each parameter. The failure to comply with these limits links the source to a specific category that varies depending on the parameter. Comparison was made between the former guidelines and those proposed in this document: former guidelines respond to health assessment and possible water rejection due to its aesthetics features, whereas the guidelines proposed respond to aqueduct operators’ requirements giving them tolls to assess feasibility of potential groundwater sources. Additional information is required to determine the start-up of groundwater sources, i.e., flow rate measurement and vulnerability, water availability, and supply and demand.